Effects of femoral rotational taping on pain, lower extremity kinematics, and muscle activation in female patients with patellofemoral pain. Issue 4 (July 2015) - Song, Chen-Yi; Huang, Han-Yi; Chen, Sheng-Chang; Lin, Jiu-Jenq; Chang, Alison H.
Abstract Objectives To explore the hip and knee joint kinematics as well as muscle activation between participants with patellofemoral pain syndrome (PFPS) and controls, and to investigate the immediate effect of proximal femoral rotational taping on pain, joint kinematics, and muscle activation during single-leg squat (SLS). Design Cross-sectional study. Methods Sixteen female participants with PFPS, and eight healthy female controls participated. Three-dimensional hip and patellar kinematics measured by electromagnetic tracking system, hip (gluteus maximus and gluteus medius) and thigh (rectus femoris) muscle activation measured by EMG, and subjective report of pain were recorded during SLS in three randomized conditions of no tape, sham taping, and femoral rotational taping with kinesiotape. Results Without taping, compared with controls, PFPS group had increased hip adduction angle (23.5 ± 11.3° vs. 15.8 ± 7.3°) during SLS. Additionally, PFPS group exhibited lesser rectus femoris activity during the initial 0–15° of SLS. Application of both femoral rotational and sham tapes reduced pain for PFPS group. Compared with no tape or sham tape, femoral rotational tape significantly shifted the patella into more posterior (1.59 ± 0.83 cm in no tape vs. 1.54 ± 0.87 cm in sham tape vs. 1.32 ± 0.72 cm in femoral rotational tape) and distal (−2.49 ± 0.95 cm vs. −2.64 ± 0.80 cm vs. −3.11 ± 0.77 cm) positions in the PFPS group. Conclusions Femoral rotational taping could alter patellofemoral kinematics and decrease pain in treatment of young female participants with PFPS.